Building health workforce capacity for planning and monitoring through the Strengthening Technical Assistance for routine immunization training (START) approach in Uganda. Issue 21 (9th May 2019) - Ward, Kirsten; Stewart, Steven; Wardle, Melissa; Sodha, Samir V.; Tanifum, Patricia; Ayebazibwe, Nicholas; Mayanja, Robert; Luzze, Henry; Ehlman, Daniel C.; Conklin, Laura; Abbruzzese, Molly; Sandhu, Hardeep S.
Highlights: Enhanced supportive supervision used to improve immunization planning and monitoring. On-the-job training and mentoring improved health care worker motivation. Routine immunization systems were strengthened by this approach. In-service training is promising for building immunization workforce capacity. Abstract: Introduction: The Global Vaccine Action Plan identifies workforce capacity building as a key strategy to achieve strong immunization programs. The Strengthening Technical Assistance for Routine Immunization Training (START) approach aimed to utilize practical training methods to build capacity of district and health center staff to implement routine immunization (RI) planning and monitoring activities, as well as build supportive supervision skills of district staff. Methods: First implemented in Uganda, the START approach was executed by trained external consultants who used existing tools, resources, and experiences to mentor district-level counterparts and, with them, conducted on-the-job training and mentorship of health center staff over several site visits. Implementation was routinely monitored using daily activity reports, pre and post surveys of resources and systems at districts and health centers and interviews with START consultants. Results: From July 2013 through December 2014 three START teams of four consultants per team, worked 6 months each across 50 districts in Uganda including the five divisions of Kampala district (45% of all districts). They conducted on-the-job training in 444 selected under-performing health centers, with a median of two visits to each (range 1–7, IQR: 1–3). More than half of these visits were conducted in collaboration with the district immunization officer, providing the opportunity for mentorship of district immunization officers. Changes in staff motivation and awareness of challenges; availability and completion of RI planning and monitoring tools and systems were observed. However, the START consultants felt that potential durability of these changes may be limited by contextual factors, including external accountability, availability of resources, and individual staff attitude. Conclusions: Mentoring and on-the-job training offer promising alternatives to traditional classroom training and audit-focused supervision for building health workforce capacity. Further evidence regarding comparative effectiveness of these strategies and durability of observed positive change is needed.